Isolated pancreatic tuberculosis: A diagnostic challenge!! - N S Harsha; S K Supreeth; P Lokesh; K Ramyasri; M Shekar; B M Suraj (Wolters Kluwer Medknow Publications, 2021)
Isolated pancreatic tuberculosis (TB) is a very rare condition even in endemic areas. Pancreatic TB is seen in immunocompromised patients and usually occurs in association with miliary TB. Pancreatic TB can present as acute or chronic pancreatitis, a pancreatic abscess, and solid pancreatic masses. In a case of pancreatic mass, the possibility of TB should be considered in the list of differential diagnoses. Endoscopic ultrasound fine-needle aspiration sampling with an acid-fast smear is required for diagnosing pancreatic TB. Early diagnosis and prompt management of pancreatic TB will prevent unnecessary surgery and associated morbidity to the patient. Hereby, we report a very rare case of isolated pancreatic TB in a 26-year-old female who presented with a mass in porta-hepatis, which was adherent to the head of the pancreas.